Chemical Imaging: Chemical Imaging Beyond the Diffraction Limit: Experimental Validation of the PTIR Technique (Small 3/2013). Issue 3 (1st February 2013) - Lahiri, Basudev; Holland, Glenn; Centrone, Andrea
<x xml:space="preserve">Abstract</x> Photothermal‐induced resonance for chemical imaging at the nanoscale is described by A. Centrone and co‐workers on page 439. An AFM cantilever measures instantaneous thermal expansion induced by light absorption in a sample. A pulsed laser, tunable across the mid‐IR is used to illuminate the sample in a total internal reflection confi guration. If the laser wavelength matches the sample vibrational absorptions, the sample heats, expands, and deflects the cantilever faster than the AFM feedback. The tip deflection is proportional to the energy absorbed, and it allows extraction of spectroscopic information with nanoscale resolution, many‐fold better than the diffraction limit. Topological images and chemical images are obtained simultaneously. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>